PEG Induces High Expression of the Cell Cycle Checkpoint Gene WEE1 in Embryogenic Callus of Medicago truncatula: Potential Link between Cell Cycle Checkpoint Regulation and Osmotic Stress - Elmaghrabi, Adel M.; Rogers, Hilary J.; Francis, Dennis; Ochatt, Sergio J. (Frontiers in Plant Science, 2017)
Polyethylene glycol (PEG) can be used to mimic osmotic stress in plant tissue cultures to study mechanisms of tolerance. The aim of this experiment was to investigate the effects of PEG (M.W. 6000) on embryogenic callus of Medicago truncatula. Leaf explants were cultured on MS medium with 2 mg L-1 NAA and 0.5 mg L-1 BAP for 5 months. Then, calli were transferred to the same medium further supplemented with 10% (w/v) 6000 PEG for 6 months in order to study physiological and putative molecular markers of water stress. There were no significant differences in growth rate of callus or mitotic index ± PEG although embryogenic potential of PEG treated callus was morphologically enhanced. Cells were rounder on PEG medium and cell size, nuclear size and endoreduplication increased in response to the PEG treatment. Significant increases in soluble sugar and proline accumulation occurred under PEG treatment compared with the control. Significantly, high MtWEE1 and MtCCS52 expression resulted from 6 months of PEG treatment with no significant differences in MtSERK1 or MtP5CS expression but down regulation of MtSOS expression. The results are consistent in showing elevated expression of a cell cycle checkpoint gene, WEE1. It is likely that the cell cycle checkpoint surveillance machinery, that would include WEE1 expression, is ameliorating the effects of the stress imposed by PEG.